Evaluation of Software Testing Techniques Using Artificial Neural Network (International Journal of Engineering and Computer Science, 2017)
Software Industry plays a vital role in the current environment, it is very essential to minimize the fault in the existing software products. In SDLC life cycle, software testing becomes very much important which finds faults in the software that increases the efficiency of software. Most of the cost is occupied by the software testing process, it is product very essential to implement the automation technique that reduces the cost that increases the software reliability. In the automated testing process, various intelligent methods are used in order to avoid the manual process. Automation testing tools can be implemented to increase the quality of the software.